Argostemma mirae (Rubiaceae) a new species from Tago, Surigao del Sur, Mindanao Island, Philippines - Blasco, Freddie A.; Tandang, Danilo N.; Alejandro, Grecebio Jonathan D. (Phytotaxa, 2024)
We describe Argostemma mirae (Rubiaceae) a new species from Mt. Tingtingan, Badong, Tago, Surigao del Sur, Mindanao Island, Philippines. It grows on a shady mossy limestone forest on a lower elevation. A. mirae resembles A. solaniflorum in having branching and pubescent stems, oblanceolate leaves, pubescent petioles, terminal to axillary inflorescence, and white corollas but differs in having shorter stems, smaller leaf blades, 4 calyx lobes and 4 corollas. Based on IUCN criteria we proposed data deficient (DD) since there is only one population currently known.